Vercellone, F., Il futuro dell´immagine, Bologna, Il Mulino, 2017. - Benéitez, Rosa (Azafea: Revista de Filosofía, 2017)
Reseña del libro Vercellone, F., Il futuro dell´immagine, Bologna, Il Mulino, 2017.